How Trump triumphed: Multi-candidate primaries with buffoons - Micael Castanheira; Steffen Huck; Johannes Leutgeb; Andrew Schotter (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
While people on all sides of the political spectrum were amazed that Donald Trump won the Republican nomination this paper demonstrates that Trump's victory was not a crazy event but rather the equilibrium outcome of a multi-candidate race where one candidate, the buffoon, is viewed as likely to self-destruct and hence unworthy of attack. We model such primaries as a truel (a three-way duel), solve for its equilibrium, and test its implications in a laboratory experiment. We find that people recognize a buffoon when they see one and aim their attacks elsewhere with the unfortunate consequence that the buffoon has an enhanced probability of winning. This result is strongest amongst those subjects who demonstrate an ability to best respond suggesting that our results would only be stronger when the game is played by experts and for higher stakes.
Keywords: C72; C92; D72; D74; 330; truel; political primaries; Trump